2007
DOI: 10.1093/sleep/30.8.997
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and C-Reactive Protein in Relation with the Severity of Obstructive Sleep Apnea Syndrome

Abstract: As a marker of nocturnal hypoxemia, ODI rather than AHI might better explain the relationship between OSAS and FMD. Because body mass index and waist-to-hip ratio were identified as risk factors of high serum CRP in OSAS, obesity should be considered when predicting cardiovascular complications in OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 40 publications
11
64
2
5
Order By: Relevance
“…This fi nding is consistent with the fi nding of a prior study. 23 The causal association between minSa o 2 and FMD is biologically plausible since endotheliumdependent vasodilation is mediated by nitric oxide, and its biosynthesis is an oxygen-dependent process. In fact, previous studies suggest that chronic sleeprelated intermittent hypoxia might have effects on vascular nitric oxide synthesis or availability.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This fi nding is consistent with the fi nding of a prior study. 23 The causal association between minSa o 2 and FMD is biologically plausible since endotheliumdependent vasodilation is mediated by nitric oxide, and its biosynthesis is an oxygen-dependent process. In fact, previous studies suggest that chronic sleeprelated intermittent hypoxia might have effects on vascular nitric oxide synthesis or availability.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This could be linked to higher oxidative stress [25][26][27], endothelial dysfunction [28][29][30], less nitric oxide production [31], and inflammation [32]. All of these pathophysiological aspects could contribute to a decreased myocardial adaptive response.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated that the relation between BMI and OSA is unclear. BMI is the traditional marker for obesity, but there has been disagreement about whether it is risk factor for OSA [6,14,17,20]. BMI was increased especially in females with OSA, but it was not correlated with AHI in polysomnography [17].…”
Section: Discussionmentioning
confidence: 99%